Case report of Double Valve Replacement with Coronary Artery Bypass Grafting with Supracoronary Ascending Aortic Replacement in a Single Patient - A Chimera - Gupta, Saikat Das; Roy, Jagadananda; Hoque, Mujibul; Mandol, Bhabesh C; Chanda, PK (Cardiovascular Journal, 2021)
Double valve replacement is now-a-days a common procedure to treat diseased cardiac valves and the primary aim of prophylactic aortic replacement during concomitant valve replacement is to prevent dreadful complication like dissection, aortic rupture and even death. Although aortic surgeries are complex and have high morbidity and mortality rates, additional double valve procedure with coronary surgery can make it even worse. But for these patients, surgery remains the one and only treatment option for symptom relieve and prolongation of life. We herein present a case of severe aortic stenosis (AS) with severe aortic regurgitation (AR) with severe mitral regurgitation (MR) with coronary artery disease (CAD) and aortic aneurysm treated successfully by us at Square Hospitals; and to our best knowledge and according to the published articles, this is probably the first time, this type of combined cardiac procedure has been accomplished along with aortic surgery, in our country. We recommend that surgeons should perform bypass grafting along with aortic replacement and valve replacement surgery when indicated, without worrying that adding such a procedure will escalate post-operative adverse effect. Cardiovasc j 2021; 14(1): 82-87